Impacts of Ownership Structure, Size, and Profitability as Moderating Factors on Stock Price - Amani, Tatik; Wilamsari, Feni; Salim, Muhammad (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2025)
This present study intends to analysis the influence of ownership structure and firm size on stock price, while considering profitability acting a moderating variable focusing on banking firms registed on Indonesia Stock Exchange (IDX) while 2021-2023 observation year. In this research, the ownership structure includes both institutional and managerial ownership, while firm size is evaluated based on total assets. Profitability is represented by ROA, and stock cost is determined by annual closing stock cost. The study applies quantitative panel regression analysis with EViews 13 software. The outcomes indicated that neither managerial nor institutional ownership significantly influenced stock prices. Meanwhile, firm size significantly impacts stock prices. Furthermore, profitability does not appear to enhance the correlation between ownership structure and the company size regarding stock price, highlighting the crucial role of financial performance in attracting investor interest. These findings provide insights for banking management and investors in gaining insight into the key elements that affect a firm’s stock market valution.